Mixed‐methods study of reported clinical cases of undesirable events, medical errors, and near misses in health care. Issue 4 (26th June 2018) - Dimova, Rositsa; Stoyanova, Rumyana; Doykov, Ilian
Abstract: Rationale, aims, and objectives: Patient safety is recognized as a key indicator of quality of medical care. International experience has shown that all efforts should focus on the delivery of a safer work environment and health care system as a whole in order to reduce or mitigate medical errors and their impact on society. The aim of this study is to investigate and classify the most common incidents regarding patient safety as well as their contributory factors, based on personal real‐life experiences and situations in medical care reported by health care professionals. Methods: A mixed‐methods study design was used. Sixty‐five respondents participated (aged from 23 to 58 y). Reported cases of undesirable events (UE), medical errors (ME), and near misses (NM) were collected, processed, and analysed based on our original conceptual framework. A qualitative content analysis and descriptive statistics were conducted on the narratives in all 34 reported valid case files. Intercoder reliability was measured through the kappa statistics (κ = .69). The overall agreement of judgments on all codes was excellent (95%). Results: A total of 29 MEs in 34 cases were reported. In 85% of them, an average of 1.83 contributory factors were identified. The most common contributory factors were "Incompetence, " "Neglect, " "Severe work overload, " and "Shortage of staff." Discussion: Important steps to prevent medical errors are their identification and reporting. Conclusion: Health care professionals appear able to report UEs, MEs, and NMs occurring in medical care practice. They seem more willing to report and distinguish incidents related to MEs than to UEs and NMs.